In situ strain evolution during a disconnection event in a battery nanoparticle1. Issue 16 (28th April 2015) - Ulvestad, Andrew; Clark, Jesse N.; Singer, Andrej; Vine, David; Cho, H. M.; Harder, Ross; Meng, Ying Shirley; Shpyrko, Oleg G.
<x xml:space="preserve">Abstract</x> Disconnection of active material is a leading cause of battery degradation. X-ray imaging suggests the formation of an interphase layer on a cathode nanoparticle leads to disconnection.